Cloreto de clorocolina (ccc) influenciando a fertilidade das gemas da videira (Vitis vinifera) cv. Itália - MOTOIKE, SERGIO YOSHIMITSU; BRUCKNER, CLÁUDIO HORST; CASALI, VICENTE WAGNER DIAS; CARDOSO, ANTONIO AMÉRICO (Revista Ceres, 2015)
.